Reviewing Retrofitting Potential for Factory Warehouse from Owner Perspective in Johor - Saidatul Aisyah Che Suhaime; Mohd Hafizal Ishak (Research in Management of Technology and Business, 2024)
Retrofitting has been commonly used to improve old structures so that they can be used for a long time. Revitalization includes adding new features to old buildings, bridges, historic sites and other constructions in addition to residences. Existing structures, especially retrofitted warehouses, can be retrofitted to strengthen their resistance to damage and structural failure. Factory warehousing has evolved into one of the most important supply chain activities. However, many studies reveal that building owners and occupants do not know how, when, or why structures should be sustainably adapted. Therefore, there are still many buildings that have not yet used the retrofit concept. The objective of the study is to determine the elements for factory warehouses in Johor and analyse the retrofitting potential of factory warehouses from the owner’s perspective. This research is focused on warehouses in Batu Pahat and Johor Bahru districts, Johor only. The methodology of this study is a qualitative approach that is by interviewing three warehouse managers to answer both research questions and has used content analysis. Researchers can determine retrofitting elements such as reducing energy consumption, renovation technology, renovation can save costs and occupy & build health used by warehouse owner and the potential of the renovation concept is very widely used by factory warehouses in Johor.